Endoscopic Findings in Loin Pain Hematuria Syndrome: Concentric Clot in Calyceal Fornices. (12th January 2009) - Canales, Benjamin K.; Windsperger, Andrew; Lukasewycz, Stephen; Monga, Manoj
Abstract : The loin pain hematuria syndrome (LPHS) creates a considerable burden, both for patients afflicted with the disease and for those involved in medical management and diagnosis. To date, the diagnosis of LPHS remains one of exclusion, with some speculation regarding the extent of actual pathology. We report ureteroscopic findings in 2 cases of LPHS. These findings provide objective confirmation of underlying pathology in a difficult-to-manage disease process.